SUPERIORS' AND SUBORDINATES' PERCEPTIONS OF PERFORMANCE: BEYOND DISAGREEMENT - Smircich, Linda; Chesser, R. J. (Academy of Management Journal, 1981)
The article discusses the results of an organizational behavior research which focused on the difference in the perceptions of job performance by superiors and subordinates. The authors state that these differences can be viewed as dysfunctional by both managers and researchers alike; managers may view such differences as a signal of ineffective or incomplete communications, while researchers view the differences as a challenge to the abundant research based on perceptual data. This research compares subordinates' perceptions of their own performance with superiors' views of performance as well as how the relationship between the superior and the subordinate may affect that perception. The research shows that subordinates do not understand their superiors' perspectives.